Identifikasi Kualitas Air Sumur, Air dalam Kemasan, dan Air Sungai dengan Metode Most Probable Number - Trisna Ayundita, Ni Putu (JURNAL BIOSHELL, 2021)
Water has a very big role, one of which is for biological needs, namely survival. The main problem faced with regard to water resources is water quality. Determination of water quality by microbiology is done by using the Most Probable Number (MPN) Test. This study used 3 samples, namely well water, bottled water, and river water. Well water contains the same amount of Coliform and Escherichia coli, namely 14 MPN / 100 mL. In the presumptive test, bottled water showed positive results, but when tested for the determination it was obtained negative results. Meanwhile, river water contains more than 1100 MPN / 100 mL of coliform bacteria and 11 MPN / 100 mL of Escherichia coli. Bottled drinking water samples are suitable for consumption, while well and river water samples are not suitable for consumption because they contain Coliform and Escherichia coli.